Effects of Adding Eubiotic Lignocellulose on the Growth Performance, Laying Performance, Gut Microbiota, and Short-Chain Fatty Acids of Two Breeds of Hens - Sun, Baosheng; Hou, Linyue; Yang, Yu (Frontiers in Veterinary Science, 2021)
Eubiotic lignocellulose is a new and useful dietary fiber source for chickens. However, few studies have been undertaken on the impacts of its use as a supplement in different chicken breeds. In this experiment, 108 Chinese native breed Bian hens (BH) and 108 commercial breed ISA Brown hens (IBH) were chosen. They were randomly divided into three groups, and 0%, 2%, or 4% eubiotic lignocellulose was added to their feed during the growing periods (9–20 weeks), respectively. We aimed to observe the impacts of adding eubiotic lignocellulose on the growth and laying performance, gut microbiota, and short-chain fatty acid (SCFA) of two breeds of hens. In this study, the addition of eubiotic lignocellulose had no significant effect on the growth performance and gut microbial diversity in the two breeds of chickens (P > 0.05). Compared with the control group, adding 4% eubiotic lignocellulose significantly increased the cecum weight, laying performance (P < 0.05), but had no significant effect on the SCFA of BH (P > 0.05); however, adding 4% significantly inhibited the intestinal development, laying performance, butyrate concentration and SCFA content of IBH (P < 0.05). Moreover, the relative abundances of the fiber-degrading bacteria Alloprevotella and butyrate-producing bacteria Fusobacterium in the 4% group of BH were significantly higher than those in the 4% group of IBH (P < 0.05), resulting in the concentration of butyrate was significantly higher than those in it (P < 0.05).. Combining these results suggests that the tolerance of BH to a high level of eubiotic lignocellulose is greater than that of IBH and adding 2%–4% eubiotic lignocellulose is appropriate for BH, while 0%–2% eubiotic lignocellulose is appropriate for IBH.